2005
DOI: 10.1115/1.1827246
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Response of Freestanding Circular Elastic Films Under Point and Pressure Loads

Abstract: This paper provides a comprehensive description of the mechanical response of freestanding circular elastic films subjected to point and pressure loads. Regimes of behavior, such as plate, linear membrane, and nonlinear membrane, are identified in terms of two dimensionless variables that allow the creation of a single map that indicates appropriate closed-form solutions. This map provides a theoretical framework to design experiments and interpret film behavior for all orders of magnitude of: film thickness-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
245
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(256 citation statements)
references
References 25 publications
11
245
0
Order By: Relevance
“…Mechanical response of such free-standing films can then fall into three distinct regimes, depending on the geometric factor h/a, applied load, and internal prestrain ε 0 . 32 Linear plate bending and prestrained membrane deflection are characterized by linear force versus deflection behavior and are valid for small loads. Which one of these two governs the mechanical behavior depends on whether stiffness generated by prestrain is greater than the bending stiffness.…”
Section: Article Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical response of such free-standing films can then fall into three distinct regimes, depending on the geometric factor h/a, applied load, and internal prestrain ε 0 . 32 Linear plate bending and prestrained membrane deflection are characterized by linear force versus deflection behavior and are valid for small loads. Which one of these two governs the mechanical behavior depends on whether stiffness generated by prestrain is greater than the bending stiffness.…”
Section: Article Cmentioning
confidence: 99%
“…32 The term linear with deflection δ, where σ 0 2D is the prestress in the membrane, corresponds to the linear, prestretched membrane regime with an internal strain of ε 0 . Finite element simulations by Lee et al 24 showed that this model can be applied to small and finite sized indenters as long as r tip , r. We extract the tip radius r tip ∼ 12 nm from SEM images, resulting in r tip /r = 0.05 in our case.…”
Section: Article Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane is comprised of natural latex rubber with a thickness of 0.006 00 and a Young's modulus of 130 pounds per square inch (psi). This highly elastic material is ideal for this cyclic loading application, and will not have a large force contribution range of strain during use [14]. This lack of force development for the range of distention provides that the pneumatic control over the compliance will be more exacting without having to account for the membrane contributions.…”
Section: Compliance Chamber Designmentioning
confidence: 99%
“…In general, a plate deflection of less than 5% of the film thickness guarantees a pure bending behaviour of the film [16]. Fig.…”
Section: Experimental Characterization Of Mechanical Propertiesmentioning
confidence: 99%